Faith and Finance: Multicultural Banks Versus Islamic Banks - Hasan, Aznan; Kalair, Omar (2010)
UM Financial in our over 5 year of retail Islamic financial products in Canada have come across many other faith groups where usury free products are requested. We are converting our current operations to a Multicultural bank which will be based on two principals 1. Usury free Products and 2. Ethical Filters. We have been approached by segments of the Christian community, specifically Amish and Mennonites sects. We also have been in contact with orthodox Jews whom wish to have usury free products. Financial product structures to the needs of a religious requirement are not unique to Muslims. The Dow Jones Dharma fund is based on Dharmic principals found in Buddhist and Hindu scriptures where such things as animal testing are not permitted. A multicultural bank would avail to the multicultural financial needs of society and be inclusive of Islamic finance. Many of the ethical filters in Islam are the same filters used by Ethical filters which go farther in protecting investors by having active debt ratios management. The Dow Jones Islamic Market Indexes and Standard and Poor Shariah Indexes debt ratio protected investors where companies such as Enron and Worldcom were delisted months before they went bankrupt. Islamic banks have worked in Muslim majority countries but in multicultural countries where Muslims are in minority a multicultural bank is a better business alternative. My paper would focus on how a multicultural bank is a more open, inclusive and inviting mode of finance vs a pure Islamic bank proposal.